Synthesis of microparticles by microfluidic emulsification for water treatment - Lian, Zheng (2020)
Microfluidics is characterised by the properties such as the minute amount of consumed materials, fast analytical and responding performances, and integration of multiple functions in the same system. Droplet microfluidic technologies have proliferated rapidly in recent years, with broad applications promoted in many industrial and biomedical fields. The microfluidic devices favour the fabrication of microparticles with versatile control over the size, morphology and compositions in a facile and economical way by manipulating the flow rates and materials of the dispersed and continuous phases. Modified off-the-shelf needle-based microfluidic devices were developed in this research to form oil-in-water (O/W) single emulsion template and fabricate various types of polydimethylsiloxane (PDMS) microparticles, including pristine PDMS microparticles (PDMS-P), two types of porous PDMS microparticles templated from tetrachloromethane (CCl4) and white granulated sugars (PDMS-C and PDMS-S, respectively), PDMS microparticles incorporating multiple-walled carbon nanotubes (PDMS-M), titanium dioxide (PDMS-T) and multiple-walled carbon nanotubes/titanium dioxide nanocomposites (PDMS-MWCNTs/TiO2). Capillary number is the ratio of viscous drag force to interfacial tension that can reflect the domination of hydrodynamic forces. The capillary number of the continuous phase for all flow conditions applied in this research was less than 0.1, suggesting the flow regime was dripping. Coefficient of variation (CV) is a measure of relative variability which is standard deviation to the mean regarding the droplet/particle sizes. CV of sizes under different flow conditions were less than 3% which indicates the particles to be highly monodispersed. The surface morphology and particle size were characterised by optical microscope and scanning electron microscope (SEM). Subsequently, the microparticles were adopted for the treatment of two types of synthetic wastewater that contained organic compounds such as toluene and Rhodamine B (RhB), respectively. It has been found that 50 mg of porous PDMS microparticles are capable of bringing down 200 ppm of the toluene-water mixture to 63 ppm within two hours. The microparticles were collected and reused thirty times with unchanged treatment capacity. Meanwhile, wastewater contained RhB dyes was treated by PDMS-M, PDMS-T and PDMS-MWCNTs/TiO2, under synergetic effects of sorption and photodegradation. The microparticles with an amount of 500 mg with 2 wt% MWCNTs/TiO2 nanocomposites incorporated could remove 38.5% of RhB through sorption in five hours and the overall removal efficiency could reach nearly 85% after photodegradation. The working efficiency of 70% can be retained even after being recycled and reused for three cycles. This research also developed a novel way using parallelisation of needle-based microfluidic systems to form highly monodispersed PDMS microdroplets with enhanced production rates yet in cost-effective way, even when forming higher-order emulsions with complex inner structure by applying commercially available two-way connectors (TWC) and 3D printed four-way connectors (FWC). The production rates of droplets could be enhanced around fourfold (over 660 droplets·min-1) to eightfold (over 1300 droplets·min-1) by TWCs and FWCs, respectively than a single droplet maker (160 droplets·min-1) to produce the same kind of droplets. Additionally, parallelisation of four-needle sets with each needle specification ranging from 34G to 20G allows for simultaneous generation of four groups of PDMS microdroplets with each group having distinct size yet high monodispersity (CV <3%). Up to six cores can be encapsulated in Water-in-Oil-in-Water (W/O/W) double emulsion using two parallelly connected devices via tuning the Capillary number of the middle phase in a range of 1.31×10-4 to 4.64×10-4. This research leads to enhanced production yields of droplets and enables the formation of groups of droplets simultaneously to meet the extensive needs of environmental applications, such as functional particles with a wide range of absorbent loadings for water treatment.